1990
DOI: 10.1038/345229a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic basis of the histo-blood group ABO system

Abstract: The histo-blood group ABO, the major human alloantigen system, involves three carbohydrate antigens (ABH). A, B and AB individuals express glycosyltransferase activities converting the H antigen into A or B antigens, whereas O(H) individuals lack such activity. Here we present a molecular basis for the ABO genotypes. The A and B genes differ in a few single-base substitutions, changing four amino-acid residues that may cause differences in A and B transferase specificity. A critical single-base deletion was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
824
2
23

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,073 publications
(859 citation statements)
references
References 29 publications
10
824
2
23
Order By: Relevance
“…Further, phenotypically relevant variants include a homozygous deletion (coverage depth ×7) at rs8176719, a T allele at rs505922 and lack of significant deletions in the RHD gene, which are characteristic of blood group O Rh-positive carriers 32,33 .…”
Section: Snp Analysismentioning
confidence: 99%
“…Further, phenotypically relevant variants include a homozygous deletion (coverage depth ×7) at rs8176719, a T allele at rs505922 and lack of significant deletions in the RHD gene, which are characteristic of blood group O Rh-positive carriers 32,33 .…”
Section: Snp Analysismentioning
confidence: 99%
“…Intron sizes were determined by PCR amplification using flanking primers followed by hybridization with specific probes to the intron products. Expression o f A transferase in Sf9 cells : The putative soluble A transferase gene was produced by RT-PCR of poly(A)+ RN A from gastric cancer cell line MKN45 using the primers EPB83/EPB90 (5-TCGAATTCGCCCCAGAAGTCTAATGCCAG and 5-TCGAATTCTGGCAGCCGCTCACGGGTTCC) located in exon III and VII, respectively (7). The DNA was cloned into the EcoRI site of pT7T3U19 (Pharmacia), followed by subcloning into the EcoRI site of the baculovirus transfer vector pACGP67.…”
mentioning
confidence: 99%
“…Their primers were overlapped at numbers 237-258 bases for a sense primer and 257-276 bases for an anti-sense primer from O-gene cDNA and they used a complex reaction mixture and a radioisotope for detection of the PCR product. Yamamoto et al (1990b) and Lee and Chang (1992) reported PCR-RFLP method. This method was used most popularly at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of ABO genotype from peripheral blood leukocytes was first presented by Yamamoto et al (1990b). Several variations were developed by using PCR-RFLP method (Lee and Chang, 1992), allele specific PCR (AS-PCR) method (Ugozzoli and Wallace, 1992), and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) method (Johnson and Hopkinson, 1992).…”
Section: Introductionmentioning
confidence: 99%